Current Status of Off-pump Coronary Artery Bypass Grafting in Patients with Multiple Coronary Artery Disease Compared with On-pump Coronary Artery Bypass Grafting: The Korean National Cohort Study - Kim, Hee Jung; Chung, Jae Eun; Jung, Jae Seung; Kim, In Seup; Son, Ho Sung (The Thoracic and Cardiovascular Surgeon, 2018)
Background Despite advance in off-pump coronary artery bypass (OPCAB) grafting, there are large debating issues regarding survival benefit between OPCAB and on-pump coronary artery bypass grafting (CABG). The aim of this study is to address appropriateness of OPCAB approach in patients with ischemic heart disease having multiple vessels using South Korea national cohort data.Methods To evaluate the safety and efficacy of OPCAB, we accessed all causes of death, late repeat revascularization, hospitalization for cerebrovascular accident (CVA), and new renal replacement therapy in patients who underwent isolated CABG with multiple grafting (≥2 grafts) and who were registered in the Korean Health Insurance Review and Assessment Service Database between April 2011 and September 2014.Results OPCAB was performed in 4,692 patients and on-pump CABG in 2,999 patients from 82 hospitals in South Korea. On multivariable analysis, on–pump CABG was associated with a significantly higher adjusted risk of overall all-cause death (hazard ratio [HR]: 1.876, 95% confidence interval [CI]: 1.587–2.216, p < 0.001) and initiation of new renal replacement therapy (HR: 1.618, 95% CI: 1.124–2.331, p = 0.009). However, we observed no significant difference in repeat revascularization and hospitalization for CVA between the two groups. In propensity score matching, matched patients (2,940 pairs) showed results similar to multivariable analysis that on-pump CABG was associated with a higher overall mortality and initiation of new renal replacement therapy (p < 0.001).Conclusion In this study, we found that OPCAB was associated with better survival rates and renal preservation compared with on-pump CABG.
Keywords: coronary artery bypass grafting; off-pump coronary artery bypass grafting; registries